Business Performance Analysis of The Banana Chips Household Industry in Konda Sub District South Konawe District - Ndaru Larasati; Yusna Indarsyih; Yusran Yusran (Jurnal Ilmiah Membangun Desa dan Pertanian, 2023)
This research was motivated by the business performance of the banana processing industry in Konda District, South Konawe Regency. The purpose of the study was to determine the magnitude of the profits of the home industry (home industry) banana processing and to know the performance of the home industry (home industry) banana processing. The population in this study was two banana-processing home industries. The sampling technique in this study used the census method so that the total population was used as a sample. The results showed that the overall profit obtained by the banana processing industry in Konda District during the current year was IDR303,837,852/year, with an average of IDR151,918,926/year. The total yield is obtained from the difference in the total amount of income of IDR540,000,000 with an average of IDR270,000,000/year with a total cost of IDR236,162,148 with a standard of IDR118,081,074/year—business performance in the banana processing industry by recording financial statements. The number of profit/loss reports on the banana processing home industry in Konda District in one production is IDR25,319,821/month. As for the output for a year, as much as IDR303,837,852/year.